Modelo Fuzzy Topsis para escolha da melhor alternativa de custos e benefícios da logística utilizando as alternativas de transporte unimodal e intermodal no escoamento do arroz - Ribeiro, Luís Otavio de Marins (2018)
The relevance of the selection of a transportation model can be easily perceived as it can impact the logistics costs of the business. In this context, transportation may account for up to 60% of logistics costs. This study aims to find an answer to the question: which is the best transportation model alternative for rice flow along the Vale do Jacuí (RS) corridor up to Praia do Forno (RJ)? The study intends to apply the Fuzzy-Topsis technique to real rice flow data after data treatment by Brainstorming with Logistics specialists. The Fuzzy-Topsis method was applied to treated data for comparison of the best transport model alternative between Unimodality of transportation using the road carriage modal and the following Intermodal alternatives: road/railway, road/waterway and road/railway/waterway. A qualitative-quantitative approach methodology was applied in the thesis. The qualitative approach is discussed in the first part, represented by literature review and the Brainstorming method; the second part presents the quantitative approach by applying the Fuzzy-Topsis technique that enabled a decision about the best cost-benefit alternative. As a result, the relevance of the use of this tool for comparison between transportation model alternatives can also be evidenced.